Geoscience and Exploration of the Argyle, Bunder, Diavik, and Murowa Diamond Deposits 2018
DOI: 10.5382/sp.20.09
|View full text |Cite
|
Sign up to set email alerts
|

The Bunder Diamond Project, India: Geology, Geochemistry, and Age of the Saptarshi Lamproite Pipes

Abstract: The Bunder diamond project comprises a cluster of seven known diamondiferous volcanic pipes and dikes known as the Saptarshi field. The largest of these is Atri, which comprises two adjacent coalesced volcanic pipes, Atri North and Atri South. This paper reports data that have been compiled into a new three-dimensional geologic model and, together with new geochemical and geochronological information, provides further insight on the internal geology, emplacement history, classification, and age of the Atri pip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…The rocks are similar to the Majhgawan lamproites and contain many vesicular pyroclasts. Mica compositions follow the lamproite trend of compositional evolution from phlogopite to tetraferriphlogopite with Ti-and Aldepletion coupled with Fe 3+ enrichment (Das et al 2018).…”
Section: Saptarshi Lamproites and The Atri Pipes Madhya Pradesh Indiamentioning
confidence: 63%
See 4 more Smart Citations
“…The rocks are similar to the Majhgawan lamproites and contain many vesicular pyroclasts. Mica compositions follow the lamproite trend of compositional evolution from phlogopite to tetraferriphlogopite with Ti-and Aldepletion coupled with Fe 3+ enrichment (Das et al 2018).…”
Section: Saptarshi Lamproites and The Atri Pipes Madhya Pradesh Indiamentioning
confidence: 63%
“…Models presented by Mathur and Singh (1971) and Rao (2007) have suggested the vent consists of concentric bands of volcaniclastic rocks all of which taper to a common focal point at unknown depth. Given the complexities of other lamproite vents, in particular the Atri Pipes (see below; Das et al 2018), revealed by recent studies, such a model is highly improbable and should be re-evaluated. The vent fill consists of diverse heterolithic olivine lamproite breccias distinguished on the basis of colour, grain size, content of xenoliths, and abundance of mica (Fig.…”
Section: Majhgawan Madhya Pradesh Indiamentioning
confidence: 99%
See 3 more Smart Citations